М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
НастяStar1
НастяStar1
06.11.2020 18:10 •  Алгебра

решите очень надо 1) без решений 2) с ними​


решите очень надо 1) без решений 2) с ними​

👇
Ответ:
Misha01923
Misha01923
06.11.2020

1.

а) 3

б) 50

в) 2,5

г) -0,7

4,5(15 оценок)
Ответ:
rozhkoff
rozhkoff
06.11.2020

1.

a)3 \\ b)50 \\ c)1 \frac{1}{4} \\ d) - 0.7

2.

{x}^{2} = 10 \\ x = + \sqrt{10} \\ x = - \sqrt{10}

\frac{1}{3} {x}^{2} = 2 \\ {x}^{2} = 6 \\ x = + \sqrt{6} \\ x = - \sqrt{6}

4 {x}^{2} - 28 = 0 \\ {x}^{2} - 7 = 0 \\ {x}^{2} = 7 \\ x = + 7 \\ x = - 7

{(x - 3)}^{2} = 9 \\ {(x - 3)}^{2} - 9 = 0 \\ (x - 3 - 3)(x - 3 + 3) = 0 \\ (x - 6)x = 0 \\ x = 6 \\ x = 0

\sqrt{x + 1} = 7 \\ x + 1 = 49 \\ x = 48

4,5(97 оценок)
Открыть все ответы
Ответ:
Kukushka2281337
Kukushka2281337
06.11.2020
2сos²x-1+cosx≥0 cosx=a 2a²+a-1≥0 d=1+8=9 a1=(-1-3)/4=-1      a2=(-1+3)/4=1/2             +                    -                        +                       -1                      1/2 a≤-1⇒cosx≤-1⇒x=π+2πn a≥1/2⇒cosx≥1/2⇒x∈[-π/3+2πn; π/3+2πn] ответ x=π+2πn и x∈[-π/3+2πn; π/3+2πn]
4,5(4 оценок)
Ответ:
Jannalizahappy
Jannalizahappy
06.11.2020

1)       ac2-ad+c3-cd-bc2+bd=  = (ac2 – ad) + (c3 –

bc2) + (bd – cd) = a·(c2 – d) + c2·(c – b) + d·(b     – c) = a·(c2 – d) +

c2·(c – b) – d·(c – b) = a·(c2 – d) + c2·(c – b) – d·(c – b) = a·(c2 –

d) + (c – b)·(c2 – d) = (c2 – d)·(a + c – b)

2)  mx2+my2-nx2-ny2+n-m= x2 ( m - n ) + y2 ( m - n ) - ( m - n ) = ( m-n ) (x2 + y2 - 1 )  

3)   am2+cm2-an+an2-cn+cn2= m2 (a + c ) + n2 ( a + c ) - n ( a + c ) = ( a+ c) ( m2 + n2 - n) 

4)   xy2-ny2-mx+mn+m2x-m2n= y2 ( x - n ) + m2 ( x - n) - m ( x - n ) = ( x-n) ( y2 + m2 - m ) 

5)   a2b+a+ab2+b+2ab+2=ab ( a + b + 2 )   + ( a+ b+ 2 ) = 2 ( a+ b + 2 ) 

6)   x2-xy+x-xy2+y3-y2=   x ( x –   y + 1) –   y 2 ( x –   y + 1)=( x –   y + 1)( x –   y 2 ).

4,4(4 оценок)
Это интересно:
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ